Functional divergence of two closely related carboxylesterases in pepper (Capsicum annuum L.) - Han, Yun-Jeong; Kang, Ha-Young; Kim, Young Soon; Kim, Jeong-Il (Plant biotechnology reports, 2023)
Carboxylesterases (CXEs) catalyze the hydrolysis of carboxylic acid esters into the corresponding acids and alcohols. Previously, a carboxylesterase gene was isolated from pepper ( Capsicum annuum L.) and designated as PepEST . This gene is highly expressed during the incompatible interaction between ripe fruits of pepper and an anthracnose fungus ( Colletotrichum gloeosporioides ), and the PepEST protein exhibits an antifungal activity by suppressing fungal growth with the inhibition of appressorium formation. In this study, a PepEST -homologous gene was newly isolated from the pepper genome, which is designated as PepEST2 (the original PepEST gene is re-named here as PepEST1 ). Compared with PepEST1 whose expression is only induced by inoculation of the fungus, PepEST2 is not induced by fungus infection, rather expressed mainly in roots. Subcellular localization analysis using tobacco protoplasts showed that both PepEST1 and PepEST2 proteins are localized in the cytoplasm, and enzymatic activity assays showed similar V max and K m values of PepEST2 to those of PepEST1. Antifungal activity assays against C. gloeosporioides demonstrated that not only PepEST1 but also PepEST2 was able to suppress the fungal growth by inhibiting the appressorium formation. In addition, the antifungal activity of PepEST2 was higher than that of PepEST1. Collectively, this study suggests that two closely related members of pepper CXEs are functionally diversified due to the differential expression patterns, and also provides PepEST2 as an alternative gene to confer disease resistance to plants.